CREATING DIAGRAMS FOR PROBLEM-SOLVING IN MATHEMATICS: IS IT WORTH THE EFFORT? - Beitzel, Brian D (PEOPLE: International Journal of Social Sciences, 2018)
Diagrams are ubiquitous in mathematics instruction. This investigation examines whether the mental effort – often referred to as cognitive load – that is required to construct and use a diagram in order to solve a problem is associated with success in arriving at accurate problem solutions. In this article, data from a series of experiments that were conducted during the past decade are re-analyzed to compare the self-rated effort of being trained to use a diagram with subsequent problem-solving performance, relative to interventions in which participants were trained to use only equations to solve the same word problems. The results demonstrate that the mental effort invested in diagram training is not uniformly beneficial across all types of mathematics problems. Specifically, diagram training is more efficacious for conditional-probability word problems than for joint- and total-probability word problems. Of particular note is the repeated finding that training in how to use Venn diagrams causes worse performance for undergraduates solving total-probability problems.